Preparation and Characterization of Nickel Oxide Thin Films by Electrostatic Spray Technique - Jamal , Raied K.; Al-Zaidi, Qahtan G.; Saeed , Nada Mohamed; Taaban, Iman N. (Iraqi Journal of Science, 2022)
A simple, inexpensive, and home–built electrostatic spray deposition (ESD) system with stable cone-jet mode was used to obtain nickel oxide (NiO) thin films on glass substrates kept at temperature of 400°C. The primary precursor solution of 0.1 M concentration hydrated nickel chloride dissolved in isopropyl alcohol. The structural, optical and electrical parameters were studied. The optical absorbance spectra for the studied samples showed its maximum around 280 nm. On the other hand, thickness interferometry measurements on the tested samples showed that film thickness was around 400 nm. The optical energy gap of the prepared NiO samples was determined to be 3.75 eV and the maximum value of refractive index was determined to be 2.1 at 350 nm.